Bifurcations : notes et matériaux - Rochefort, Jean-Claude (Ciel variable)

(untitled) (Les Productions Ciel variable, 2005)
Abstract The author observes, first, that the artist maintains an emotional relationship with nature and that an ontology of the landscape is manifested in her work because there is a profound connection between the type of regard cast upon the objects of the sensory world and the final rendering of the chosen mode of representation. Second, the author compares photographic writing and self-analysis. Based on Inconsciences, the author emphasizes the importance of articu-latory strategies in these discontinuous sequence of images. These zones of passage are decisive in the exploration both of self and of photographic language, since this is precisely where stumbling blocks might arise.